Analisis Pola Terciptanya Gol pada Turnamen Sepak Bola Waena Cup 2023 Jayapura - Mangolo, Ewendi; Hutajulu, Pahala Tua (Jurnal Sporta Saintika, 2023)
The aim of the research was to analyze the goals scored in the Waena Cup Tournament 2023, which took place in Jayapura City from 19 February 2023 to 26 March 2023. The sample of this research was composed of 40 games played and 89 goals scored in the preliminary round. Analysis of goal patterns was carried out using a statistical approach, limited to five situations, namely: set play, build up, build up, direct play and counter attack. Furthermore, the impact of the first goal was also given. Data was analyzed using descriptive statistics of discrete frequencies with a reliability index of 1.00. The highest frequency of goal pattern was from counter-attacks at 43%, followed by set plays at 31% and rebuilds at 18%. Meanwhile, the lowest frequencies of goal pattern were from direct play and build up, with frequencies of 4% and 3% respectively. Players also gain a significant psychological advantage from the first goal in a match, with 77% of first goals resulting in winning. It can be concluded that in the 2023 Waena Cup Tournament, football players in Jayapura have the characteristics of scoring goals through fast and spontaneous actions supported by dribbling ability and running speed. The results of this research provide a recommendation that it is necessary to provide special sessions for set-play training and direct attacks to increase the chances of winning.